Fabrication and properties of superparamagnetic UV-curable nanocomposites based on covalently linked waterborne polyurethane/functionalized hollow Ni0.3Zn0.5Fe2O4 microspheres. Issue 59 (28th June 2015) - Chen, Suli; Wu, Wenling; Zhao, Guanghui; Jin, Tao; Zhao, Tianqi
<x xml:space="preserve">Abstract</x> A superparamagnetic and well-dispersed nanocomposite has been successfully synthesized via an in situ polymerization method using hollow Ni0.3Zn0.5Fe2O4 nanoparticles (h-NZFO) as a filler and waterborne polyurethane (WPU) as a matrix.